THE FERMENTED SWEET POTATO FLOUR - Deary Amenthy Zahrotinufus Joen; Giffary Pramafisi Soeherman; Fahrulsyah Fahrulsyah (Politeknik Negeri Lampung, 2022)
Sweet potatoes ( Ipomea batatas L.) is a source of carbohydrates. The high carbohydrate content makes sweet potatoes very potential to be processed into flour. However, naturally processed sweet potato flour has some drawbacks when applied to food. To overcome this problem, it is necessary to modify the processing process for sweet potato flour. One way to modify flour can be done by fermentation using Lactic Acid Bacteria (BAL). The principle of modification by fermentation in a spontaneous way that is thought to grow is Lactic Acid Bacteria (BAL) which produce pektinolytic and sellulolytic enzymes that can destroy the cell walls of yams so that starch hydrolysis occurs. In addition, the duration of fermentation will affect the fermentation results. The purpose of this experiment was to determine the effect of spontaneous fermentation on the color of sweet potato flour.